Procurement and contract strategies for construction - Heaphy, Ian (ICE Publishing, 2022)
This resource provides detailed guidance on the key steps in the procurement process and the decisions which need to be made in order to create an effective procurement and contract strategy. Essential reading for a broad range of construction professionals, particularly commercial, contractual and procurement staff, it will also be of interest to students on university and professional courses which cover procurement and contract strategy.